(untitled) (Journal of the College of Basic Education, 2023)
The adsorption studies of methane as environmental pollutant gas on PVA surface was discussed as one of the gas-solid application and removed it from the atmosphere .The adsorption ability of the methane gas at temperature rate 20 , 30, 40 and 50 o C was investigated .The results revealed that the relation between the gas concentration versus adsorption capacity obeys Freundlich isotherm .The a & n values were calculated was increases with the decreases of the temperatures ,this referred that the adsorption was physical adsorption .The adsorption isotherms was investigated from the relation between 1/T versus ln x furthermore the ∆H values was calculated according to Clauses-Clapeyron equation in these range of temperatures.